2022
DOI: 10.1097/cce.0000000000000700
|View full text |Cite
|
Sign up to set email alerts
|

Post-Intensive Care COVID Survivorship Clinic: A Single-Center Experience

Abstract: OBJECTIVES: Patients discharged from the ICU post-COVID-19 pneumonitis may experience long-term morbidity related to their critical illness, the treatment for this and the ICU environment. The aim of this study was to characterize the cognitive, psychologic, and physical consequences of COVID-19 in patients admitted to the ICU and discharged alive. DESIGN: Prospective cohort study. SETTING: Post-intensive care syndrome (PICS) follow-up clinic at Tallaght University Hospital, a tertiary referral center with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recently, in a prospective study of 22 patients conducted in Ireland, Apache II strongly correlated with the MoCA at 6 months. 26 In a linear regression analysis, the authors observed that for each point that Apache II increases, the MoCA score decreases by 1.6 points (Coefficient β: −1.6, p: 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in a prospective study of 22 patients conducted in Ireland, Apache II strongly correlated with the MoCA at 6 months. 26 In a linear regression analysis, the authors observed that for each point that Apache II increases, the MoCA score decreases by 1.6 points (Coefficient β: −1.6, p: 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…All the included studies were published from 2021 to 2023 (Table 1 ). Two studies [ 23 , 32 ] were conducted in the United States, 16 in Europe [ 15 , 17 , 18 , 20 - 22 , 24 - 31 , 33 , 34 ], one in Brazil [ 16 ], and one in Australia [ 19 ]. Four studies [ 16 , 25 , 26 , 33 ] assessed return-to-work in patients receiving ECMO.…”
Section: Reviewmentioning
confidence: 99%
“…A total of 42 studies were assessed; 20 studies involving 1254 patients were included in the quantitative synthesis and 19 studies were used for the meta-analysis. The number of studies (i.e., number of patients) reporting an instance of return-to-work at 0-3 months, 4-6 months, and 7-12 months were three [15][16][17], eleven [18][19][20][21][22][23][24][25][26][27], and eight [17,25,[27][28][29][30][31][32], respectively. Studies in which outcome assessments were conducted over an extended time frame were excluded.…”
Section: Study Selectionmentioning
confidence: 99%
“…A prospective cohort study conducted in Spain in 2021, evaluating the sequelae occurred at the first month after hospital discharge among patients who required ICU admission for severe COVID-19 pneumonia, concluded that these patients need a long-term follow-up due to its expected bad prognosis, and this should be extended beyond 30 days after ICU discharge [ 6 ]. However, evidence regarding the optimal duration for follow-up care in individuals who have survived COVID-19 after being admitted to the ICU is still lacking [ 7 ]. The present study aimed to assess early and late mortality after ICU discharge among surviving critical COVID-19 patients and describe their most relevant predictors, in order to propose recommendations regarding the most appropriate follow-up strategy for COVID-19 ICU survivors.…”
Section: Introductionmentioning
confidence: 99%